Diretrizes para proposição de planos de segurança da água em sistemas de abastecimento municipais goianos - Braga, Rafaela Jacob de Oliveira (2015)
Water supply systems (WSS) for human consumption aim to produce and supply drinking water to the population through the distribution network. However, the need to revise the actuals methodological procedures that maintain the water quantity and water quality in satisfactory levels for domestic consumption has caused the World Health Organization to propose a new methodology called Water Safety Plan (WSP), still incipient at state of Goiás. In this way, this study aims to propose Safety Plan of Water to 21 cities located at the state of Goiás that presenting WSS managed by local governments. The study was divided into two chapters. The first chapter characterized the WSS of this 21 cities in the state of Goiás, including the collect, treatment and distribution of treated water, and identified ways of managing providers of sanitation services. It was observed that 61% of the supply systems provide by surface water supply system (SWSS). Mixed water supply systems (MWSS) and underground water supply system (UWSS) found up to 50% non-specific departments and 50% for the departments, respectively. Regarding the source of supply, it was noted that the worst results for the quality of supply source were assigned by the WSS managed by non-specific sanitary services departments. Only the cities Abadiânia, Corumbá de Goiás, Mineiros, Rio Quente, Trombas, Caldas Novas, Catalão, Panamá and Senador Canedo add fluorine to their treated water. In relation of the reservation and distribution system of treated water, there is the prevalence of elevated tanks. The worst scenarios for the reservation system and treated water distribution were found at the cities Cachoeira de Goiás, Guarinos, Mossâmedes, Nova Roma, Paranaiguara and São Simão. It was concluded that the WSS have diverse scenarios regarding the treatment of the water and the planning monitoring and maintenance of them are deficient. The second chapter identified the elements of risk perceived by the population associated with water resources. They evaluated the dangerous events by qualitative and quantitative techniques applied to goianos WSS managed by the own cities. The WSS were evaluated by collect system component, raw water reservoir and adduction (A); water treatment system (B); reservation system and distribution of treated water (C). The studied cities that have more high and very high risk, considering all components of the systems, are Cachoeira de Goiás, Guarinos, Mossâmedes, Nova Roma, Paranaiguara and São Simão. Regarding the UWSS, it seems that the A system component registered the same percentage to Cachoeira de Goiás and Guarinos. The B and C system components registered 62.5% and 50% at Cachoeira de Goiás and 75% and 78.5 % at Guarinos. The MWSS with the highest percentage of high and very high risks were situated at the cities Santa Rita do Novo Destino and Nova Roma (52.4 % for question A). Mossâmedes and Nova Roma were the cities that had the highest number of high risks and too high risks for the components B and C in MWSS. The cities Paranaiguara and São Simão had UWSS with the highest number of high and very high risk. The WSS at cities in the state of Goiás managed by the own cities feature deficiencies in the safe management of the water distributed to the population. It is necessary to adopt methodologies that addresses all components of the WSS regardless of system type.